A preclusão no processo de arbitragem - Tamaki, Luiz Henrique (2016)
This dissertation work proposes a brief study of the estoppel, as well as a review of the arbitration process, in order to finish up on the existence and applicability of estoppel in the arbitration process. To this end, we will briefly comment on the institutes of estoppel and the arbitration process, tracing its logical precepts and introducing the combination of both concepts